Potential of Immune-Related Therapy in COVID-19 - Yuan, Chunjue; Li, Ruoyun; Liu, Guohong; Pan, Yunbao (Frontiers in Pharmacology, 2021)
At the beginning of 2020, a sudden outbreak of new coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection led to anxiety, panic, and crisis among people worldwide. The outbreak first occurred in Wuhan, China, in late December 2019 and then spread rapidly across the globe, thus becoming a major public health emergency. Although the current epidemic situation in China tends to be stable, coronavirus disease 2019 (COVID-19) continues to spread globally. At present, no specific therapeutic drugs and vaccines are available against COVID-19. Also, the pathogenesis of the SARS-CoV-2 is not fully clear. Human immunity is important in SARS-CoV-2 infection. Studies have shown that excessive inflammation caused by SARS-CoV-2 infection and subsequent induced uncontrolled cytokine storm are the main causes of disease deterioration and death of severe patients. Therefore, immune-related research is of great significance for the prevention, control, and prognosis of COVID-19. This study aimed to review the latest research on immune-related therapy in COVID-19.